Fabrication of Hyaluronan-Poly(vinylphosphonic acid)-Chitosan Hydrogel for Wound Healing Application. (6th April 2016) - Hoang Phuc, Dang; Thi Hiep, Nguyen; Ngoc Phuc Chau, Do; Thi Thu Hoai, Nguyen; Chan Khon, Huynh; Van Toi, Vo; Dai Hai, Nguyen; Chi Bao, Bui
Abstract : A new hydrogel made of hyaluronan, poly(vinylphosphonic acid), and chitosan (HA/PVPA/CS hydrogel) was fabricated and characterized to be used for skin wound healing application. Firstly, the component ratio of hydrogel was studied to optimize the reaction effectiveness. Next, its microstructure was observed by light microscope. The chemical interaction in hydrogel was evaluated by nuclear magnetic resonance spectroscopy and Fourier transform-infrared spectroscopy. Then, a study on its degradation rate was performed. After that, antibacterial activity of the hydrogel was examined by agar diffusion method. Finally, in vivo study was performed to evaluate hydrogel's biocompatibility. The results showed that the optimized hydrogel had a three-dimensional highly porous structure with the pore size ranging from about 25  µ m to less than 125  µ m. Besides, with a degradation time of two weeks, it could give enough time for the formation of extracellular matrix framework during remodeling stages. Furthermore, the antibacterial test showed that hydrogel has antimicrobial activity against E. coli. Finally, in vivo study indicated that the hydrogel was not rejected by the immune system and could enhance wound healing process. Overall, HA/PVPA/CS hydrogel was successfully fabricated and results implied its potential for wound healing applications.